A gramática do design visual: uma proposta de leitura de fotografia documental - SANTOS, Gabriela Rodrigues dos (2019)
The following work is entitled “The grammar of visual design: a proposal of reading documentary photography”, having its research focused on the Grammar theory of Visual Design, by Kress and Van Leeuwen (2006), with the objective of analyzing the multimodality present in the documentary photographs, revealing the meanings in this genre, such as the use of photographs from the context of the Brazilian military regime, exposing discourses materialized in the nonverbal context about events of the time. The corpus consists of photographs used for teaching / learning in textbooks and also as a way of understanding the past. The analyzed images are of dictatorial events in Brazil that, even with censorship and repression, were not prevented from photographing, as a form of learning for the future. The methodology used in this study is of the GDV within the representational, interactional and compositional functions proposed by Kress and Van Leeuwen (2006), considered essential for the analysis of multimodal texts. As a result, a greater understanding of the student, from the visual use, to analyze the contributions of these photographs for the reconstruction of the facts narrated about the military dictatorship in the context of the textbook.